Exploring relationship satisfaction between global professional service firms and local clients in emerging markets - Dou, Wenyu; Li, Hairong; Zhou, Nan; Su, Chenting (Journal of International Business Studies, 2010)
Extending the perspective of agency theory, this study incorporates both professional and local knowledge asymmetry into a model of relationship satisfaction between global professional service firms and their local clients. The model also includes learning orientation and adaptation that are theorized to regulate the impact of knowledge asymmetry on goal incongruence, which ultimately affects relationship satisfaction. China was selected as the setting of the study because it is the largest emerging market, has seen double-digit growth of advertising expenditures for the past two decades, and is home to many multinational advertising agencies that have increasingly pursued local clients as revenue sources. Multiple informants from 177 domestic Chinese firms and their multinational advertising agencies were personally interviewed, and the dyadic data were used to test the model. Results show that both types of knowledge asymmetry lead to goal incongruence, which causes client dissatisfaction. The role of learning orientation varies, as does the role of adaptation, in moderating the impact of knowledge asymmetry on goal incongruence and the impact of goal incongruence on relationship satisfaction. Theoretical and managerial implications of the findings are discussed, along with the limitations of the study and future research directions.